Acute naltrexone does not remediate fronto‐striatal disturbances in alcoholic and alcoholic polysubstance‐dependent populations during a monetary incentive delay task. (6th September 2016) - Nestor, Liam J; Murphy, Anna; McGonigle, John; Orban, Csaba; Reed, Laurence; Taylor, Eleanor; Flechais, Remy; Paterson, Louise M; Smith, Dana; Bullmore, Edward T; Ersche, Karen D; Suckling, John; et al.
Abstract: There is a concerted research effort to investigate brain mechanisms underlying addiction processes that may predicate the development of new compounds for treating addiction. One target is the brain's opioid system, because of its role in the reinforcing effects of substances of abuse. Substance‐dependent populations have increased numbers of the mu opioid receptor (MOR) in fronto‐striatal regions that predict drug relapse, and demonstrate disturbances in these regions during the processing of non‐drug rewards. Naltrexone is currently licensed for alcohol and opiate dependence, and may remediate such disturbances through the blockade of MORs in fronto‐striatal reward circuitry. Therefore, we examined the potential acute modulating effects of naltrexone on the anticipation of, and instrumental responding for, non‐drug rewards in long‐term abstinent alcoholics, alcoholic poly substance‐dependent individuals and controls using a monetary incentive delay (MID) task during a randomized double blind placebo controlled functional MRI study. We report that the alcoholic poly substance‐dependent group exhibited slower and less accurate instrumental responding compared to alcoholics and controls that was less evident after acute naltrexone treatment. However, naltrexone treatment was unable to remediate disturbances within fronto‐striatal regions during reward anticipation and 'missed' rewards in either substance‐dependent group. While we have not been able to identify the underlying neural mechanisms for improvement observed with naltrexone in the alcoholic poly‐substance dependent group, we can confirm that both substance‐dependent groups exhibit substantial neural deficits during an MID task, despite being in long‐term abstinence. Abstract : Opioid disturbances within dopamine fronto‐striatal reward circuitry may confer an ongoing risk for relapse to drug rewards if there is a diminished incentive value of, and motivation to procure, non‐drug rewards. Here, we show that acute naltrexone treatment does not remediate disturbances in fronto‐striatal regions during non‐drug reward anticipation in long‐term abstinent alcoholic and polysubstance‐dependent groups.